Investigation on the effects of Aspergillus nigerin sustainable bio-micromachining of copper. (2021) - Sekar, T.; Hemalatha, B.; Rajeswari, B.; Surendran, R.; Vijay, M.
Abstract: Generally, the components of Micro and Nano electromechanical systems (MEMS and NEMS) are fabricated by conventional and environmental hazardous machining techniques like Chemical/Photochemical, Electric Discharge, Laser beam etc. This work attempts to investigate the effects of Aspergillus niger, a fungus on micro-machining of pure copper without any heat affected zone and environmental hazardous free. Aspergillus niger spores was acquired from Tamil Nadu Agriculture University, Coimbatore and its culture was developed at the laboratory. The major influencing parameters of shaking speed, temperature, time and pH are considered to evaluate the performance of bio-micromachining in terms of micro hardness and specific metal removal rate at 15th day. The result was analysed using SEM images and this research novelty revealed that the reduction of micro hardness of bio-micro machined copper from 103.53 HV0.5 to 97.5 HV0.5 i.e. reduction of 5.82% was achieved by Aspergillus niger fungus. Also, the specific material removal rate was found as 0.0197 mg/h.cm 2 which prove the potential ability of this process in fabricating MEMS and NEMS components.